Fiscal policy and the cycle in the euro-area : the role of government revenue and expenditure - Turrini, Alessandro 1966- (European Economy. Economic papers, 2008)
This paper analyses the cyclical behaviour of fiscal policy in euro-area countries over the 1980-2005 period, focusing on the distinct role of government revenue and expenditure. The estimation of separate fiscal policy reaction functions in good and bad times reveals that, controlling for other factors, the average stance of fiscal policy is expansionary when output is above potential, thus denoting a pro-cyclical bias in good times, while no strong evidence of a cyclical bias is found in bad times. The separate estimation of reaction functions for revenue and expenditure policy indicates that this pro-cyclical bias is an entirely expenditure-driven phenomenon. Probit regressions also reveal that the risk of pro-cyclicality in good times stems from expenditure behaviour, since expenditure-based budgetary adjustment is a highly significant determinant of the probability of pro-cyclical fiscal policy in good times. The separate estimation of fiscal reaction functions in EU countries with strong and weak expenditure rules provide some support to the view that expenditure rules can be helpful to curb the expansionary bias of expenditure policy in good times.